Galectin-3 as a new negative checkpoint of the immune response is the key target for effective immunotherapy against prostate cancer - Tiraboschi, Carolina Daniela (2019)
Prostate cancer (PCa) is a major health problem worldwide. Taxol derivatives–based chemotherapies or immunotherapies are usually proposed depending on the symptomatic status. In the case of immunotherapy, tumors develop robust immune escape mechanisms that abolish any protective response. However, Docetaxel has been shown to enhance the effectiveness of immunotherapy in a variety of cancers, but to date, the mechanism is still unknown. Herein, we showed first that Galectin-3 (Gal-3) expressed by prostate tumor cells is the principal immunological checkpoint responsible of the failure of immunotherapy; and that Docetaxel leads to the inhibition of Gal-3 expression in PCa cells as well as in clinical samples of mCRPC patients promoting a Th1 response. We thus optimized a prostate cancer animal model that undergoes surgical resection of the tumor like prostatectomy to mimic what is usually performed in patients. More importantly, using low and nontoxic doses of taxane prior to immunotherapy, we were able to directly impact the activation and proliferation of CD8+ cytotoxic T cells through reducing the number of CD8+CD122+CD28-T cells and highly control tumor recurrence. Thus, Gal-3 expression by PCa cells is a key inhibitor for the success of immunotherapy, and low doses of Docetaxel with noncytotoxic effect on leukocyte survival should be used prior to vaccination for all PCa patients. This combined treatment sequence right after surgery would promote the preconditioning of the tumor microenvironment, allowing for effective anti-tumor immunotherapy and can be transferred rapidly to clinical therapeutic protocols.